Clinico-radiological correlation of reverse shoulder arthroplasty outcomes - Elshahhat, Amr; Selim, Naser; Basyoni, Yehia; Nour, Khaled (International Journal of Research in Orthopaedics, 2022)
Positioning of prosthetic components is essential for the success and longevity of the prosthesis. Judging prosthetic implantation radiologically is always beneficial; plain radiographs and computed tomography can provide information regards inclination and version of glenoid component, besides, lateralization of prosthetic components. This study aims at postoperative radiological evaluation of component positioning of reverse shoulder prosthesis and correlating measured radiological parameters with clinical outcome. Radiological assessment was carried on by radiographs taking advantage of true anteroposterior projection, and midaxial two-dimensional computed tomography cut. Radiographs evaluated glenoid inclination in coronal plane (superior-inferior tilt) via global inclination angle, and critical shoulder angle. Center of rotation was evaluated by calculating acromion index. Additionally, acromiohumeral interval, and deltoid lever arm distance were documented. Midaxial CT cuts evaluated glenoid version. Each parameter was correlated to postoperative clinical outcome represented in range of motion and total functional scores. the mean acromion index revealed significant change to 63.82±9.06%, total medialization surged significantly with average 1.51 cm with a mean postoperative calibrated center of rotation-distance of 3.72±0.78 cm. The mean increase in acro-mio-humeral interval was 1.57 cm with a new postoperative value of 2.49±0.9 cm. The mean glenoid version declined to 5.7º±5º, however, this change was not significant. In conclusion, accurate positioning of shoulder prosthesis components with proper tensioning of soft tissue envelope within acceptable measurement parameters is considered crucial for stability and longevity of implant with the best clinical outcomes.